Cyclodextrins Core Concepts and New Frontiers - Ali, Rashid (IntechOpen, 2023)
Cyclodextrins (CDs) have attracted great interest from the research community as well as industries in an array of sectors because of their unique structural features. This book provides a comprehensive overview of CDs, beginning with their historical background. Chapters address such topics as the structure and physiochemical properties of CDs, advancements in the field, and potential applications of these materials in fields such as drug delivery and sensing. This book reveals new frontiers in the CD world and is a useful resource for organic, analytical, and supramolecular chemists as well as scientists engaged in biological and material sciences.